Enhancement of wavefront measurement sensitivity in a zonal wavefront sensor without curtailing the sensing speed. (16th December 2021) - Kumar, Nagendra; Khare, Alika; Boruah, Bosanta R
Abstract: In this paper we propose a zonal wavefront sensing scheme that facilitates wavefront measurement with enhanced sensitivity at the standard video rate. We achieve this enhanced sensitivity by implementing a sequential display of binary holograms described over each zone sampling the incident wavefront with the help of a ferroelectric liquid crystal spatial light modulator. By keeping the number of active zones as 24 and using a camera with an imaging frame rate equal to the binary hologram display rate of the spatial light modulator, we are able to reach a sensing frame rate of 60 Hz. In addition to enhanced sensitivity, the proposed scheme facilitates zone-wise tuning of binary holograms and eliminates the possibility of any crosstalk between adjacent zones. We perform a proof-of-principle experiment that validates the proposed zonal wavefront sensing scheme and demonstrates its advantages.